Perbedaan Tingkat Keparahan Gingivitis pada Siswa Kelas VII di Sekolah Menengah Pertama Negeri 3 Gianyar dengan Sekolah Menengah Pertama Kesuma Sari Denpasar Tahun 2025 - Surya Kencana, I Gede; Gejir, I Nyoman; Artawa, I Made Budi (Jurnal Kesehatan Gigi (Dental Health Journal), 2025)
Oral and dental diseases are common in communities worldwide. Although there are many types of oral and dental diseases; cavities, or dental caries, and periodontal disease are the leading oral and dental problems in many countries. The purpose of this study was to analyze and compare the severity of gingivitis at SMP Negeri 3 Gianyar (public) and SMP Kesuma Sari Denpasar (private), to determine whether there are significant differences in the severity of gingival inflammation. This study used an observational analytical method with a cross-sectional design. The study population was all students at SMP Negeri 3 Gianyar and SMP Kesuma Sari Denpasar. Sampling was conducted using a purposive sampling technique. The results of the study showed that the gingivitis level at SMP Negeri 3 Gianyar was healthy (6%, 17%, 20%, 55%, 9%, 25%, and 1%, respectively), while at SMP Kesuma Sari Denpasar the level was healthy (3%, 10%, 5%, 16%, 15%, 48%, and 8%, respectively), with mild inflammation. The Chi-Square test found a significant relationship between school type and the Gingival Index Criteria (Sig. ≤ 0.05). This indicates that the severity of gingivitis in public and private junior high school students differs significantly. The conclusion is that students at SMP Kesuma Sari Private tend to have higher levels of gingivitis than students at SMP Negeri 3 Gianyar.